2020
DOI: 10.1017/s0954579420000280
|View full text |Cite
|
Sign up to set email alerts
|

A mother–child intervention program for adolescent mothers: Results from a randomized controlled trial (the TeeMo study)

Abstract: Abstract Children of adolescent mothers are a high-risk group for negative child development. Previous findings suggest that early interventions may enhance child development by improving mother–child interaction. The purpose of the current study was to evaluate a mother–child intervention (STEEP-b) program in high-risk adolescent mother–infant dyads (N = 56) within a randomized controlled trial (RCT). Mother–child interaction was assessed at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 79 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…Due to limited studies and high heterogeneity, we were unable to pool parenting stress outcomes through meta-analysis. Five of these studies were in favor of AE in reducing parenting stress (Adkins et al, 2021 ; Baker et al, 2015 ; Firk et al, 2020 ; Opiola & Bratton, 2018 ; Sprang, 2009 ) and two found no statistically significant difference between AE and the comparator condition in reducing parenting stress (Ozturk et al, 2019 ; Spieker et al, 2012 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Due to limited studies and high heterogeneity, we were unable to pool parenting stress outcomes through meta-analysis. Five of these studies were in favor of AE in reducing parenting stress (Adkins et al, 2021 ; Baker et al, 2015 ; Firk et al, 2020 ; Opiola & Bratton, 2018 ; Sprang, 2009 ) and two found no statistically significant difference between AE and the comparator condition in reducing parenting stress (Ozturk et al, 2019 ; Spieker et al, 2012 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The AAP policy statement emphasizes that family-centered pediatric medical homes (FCPMH) are integral to the universal promotion of ERH. 1 Despite this, only three identified RCTs 91,99,102 were implemented by pediatricians or in FCPMH. Also, a majority of studies in this review focused on biological mothers and parent/caregiver-infant dyads at high risk of impaired ERH.…”
Section: Discussionmentioning
confidence: 99%
“…The EA-Z is scored on a 100-point scale that is divided into four categories: (a) emotionally available, (b) complicated, (c) detached, and (d) problematic/disturbed (Wurster et al, 2019). These categories correlate with the four attachment styles: secure, insecure-anxious, insecure-avoidant, and insecure-disorganized, respectively 91,195,199 .…”
Section: Emotional Availability Scales (Eas) and Emotional Attachment...mentioning
confidence: 99%
“…Her main research interests are eating disorders in childhood and adolescence, especially AN. She has conducted several clinical trials among which are the ANDI study [ 39 ], the Home Treatment study [ 40 ] and the TeeMo-study (study on adolescent mothers and their children; [ 64 ]).…”
Section: Authors’ Informationmentioning
confidence: 99%